1996
DOI: 10.1148/radiology.201.1.8816547
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis: usefulness of color Doppler US.

Abstract: Hyperemia in the wall of the appendix at color Doppler US is a sensitive indicator for inflammation. A simple additional color Doppler US examination may be helpful in the diagnosis of early acute appendicitis when an appendix is well depicted and is equivocal in size at gray-scale US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 0 publications
5
30
0
1
Order By: Relevance
“…Our prospective real-time US assessment of the appendix and of inflammatory changes in the right lower abdominal quadrant was based on a set of eight criteria derived from reports in the literature (9,15,16): enlarged appendix, fluid in the appendiceal lumen, lack of compressibility of the appendix, color in the appendiceal wall on color Doppler US images, inflammatory changes in perienteric fat in the right lower quadrant, cecal wall thickening, right lower quadrant lymph nodes, and peritoneal fluid. The appendix was considered enlarged when its outer anteroposterior diameter under compression, measured in the transverse plane, was 6 mm or larger.…”
Section: Discussionmentioning
confidence: 99%
“…Our prospective real-time US assessment of the appendix and of inflammatory changes in the right lower abdominal quadrant was based on a set of eight criteria derived from reports in the literature (9,15,16): enlarged appendix, fluid in the appendiceal lumen, lack of compressibility of the appendix, color in the appendiceal wall on color Doppler US images, inflammatory changes in perienteric fat in the right lower quadrant, cecal wall thickening, right lower quadrant lymph nodes, and peritoneal fluid. The appendix was considered enlarged when its outer anteroposterior diameter under compression, measured in the transverse plane, was 6 mm or larger.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that color Doppler sonography can be used to help diagnose early appendicitis. Blood vessels within the inflamed appendix and surrounding mesoappendix show an increase in size and number, which is a sensitive indicator of inflammation [22,23]. Using color Doppler sonography to detect appendicitis can produce a sensitivity of 87%, specificity of 97%, and accuracy of 93% [23].…”
Section: Discussionmentioning
confidence: 99%
“…A Without intravenous contrast, an ill-defined area of soft-tissue attenuation with a central focus of low attenuation is seen in the right lower quadrant (arrows). B Contrast enhancement of the wall of the appendix (arrows) helps distinguish it from adjacent edema provides a noninvasive method of assessing hyperemia in the inflamed appendix and surrounding tissues [16,17,18]. The color flow pattern changes during the course of appendicitis, from hypervascularity of the inflamed portion of the appendix in the acute stage to decreasing vascularity as necrosis and perforation ensue.…”
Section: Need For Contrast Administrationmentioning
confidence: 99%